2019
DOI: 10.4110/in.2019.19.e35
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Elevates TFH Cells and Germinal Center B Cell Response for Antibody Production in Mice

Abstract: Curcumin is a natural product extracted from Curcuma longa. It has been reported as a potent antioxidant and anti-inflammatory compound. Previous studies have demonstrated that curcumin suppresses pro-inflammatory cytokine production via inhibition of NF-κB in macrophages. However, its role in adaptive immune cells such as T cells, in vivo, has not clearly been elucidated. Here, we examined the effects of curcumin in T follicular helper (T FH) cells and on Ab production during NP-ovalbumin immunization in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…injected daily until day 6 ( C. longa ) In mice, curcumin significantly increased CXCR5 + B-cell lymphoma 6+ TFH cells and CD95+ GL-7+ germinal center B cells in draining lymph nodes. Total Ab production as well as high affinity Immunoglobulin G (IgG1 and IgG2b) Ab production was induced Preclinical in vivo [ 35 ] Tetrahydrocurcumin (THC) 120 mg/kg per day, and 1 kg of the AIN 93 G diet contained 800 mg of THC, day 0 to day 25 ( C. longa ) THC had beneficial effects on 13 asthmatic mice such pathological changes (eosinophils hyper-production), Th17 and T cell subsets and attenuating the Th2 response Preclinical in vivo [ 60 ] Diet containing 1% curcumin until the end of the study ( C. longa ) In New Zealand Black/White F1 female mice starting at 18 weeks of age with lupus nephritis (LN), curcumin induced the protective effects at least in part by its interaction with regulatory T (Treg) cells Preclinical in vivo [ 18 ] Trans-anethole (FEO) (130 mg/kg FEO, thrice weekly for 1 week, by rubbing on shaved rat dorsal area) ( Foeniculum vulgare Mill. – Apiaceae) In six rats, hepatic dysfunction study indicates promising significant amelioration of liver function reflected in ALT, AST, alkaline phosphatase (ALP), bilirubin, albumin plasma levels by FEO treatment Preclinical in vivo [ 47 ] Trans-anethole (FEO) (36.4, 72.8 or 145.6 mg/kg) once per day for 7 consecutive days ( F. vulgare ) In acute lung injury (ALI)-bearing mice, FEO treatment eliminated LPS‑induced histopathological changes, decreased the number of inflammatory cells, and reduced in IL-17 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…injected daily until day 6 ( C. longa ) In mice, curcumin significantly increased CXCR5 + B-cell lymphoma 6+ TFH cells and CD95+ GL-7+ germinal center B cells in draining lymph nodes. Total Ab production as well as high affinity Immunoglobulin G (IgG1 and IgG2b) Ab production was induced Preclinical in vivo [ 35 ] Tetrahydrocurcumin (THC) 120 mg/kg per day, and 1 kg of the AIN 93 G diet contained 800 mg of THC, day 0 to day 25 ( C. longa ) THC had beneficial effects on 13 asthmatic mice such pathological changes (eosinophils hyper-production), Th17 and T cell subsets and attenuating the Th2 response Preclinical in vivo [ 60 ] Diet containing 1% curcumin until the end of the study ( C. longa ) In New Zealand Black/White F1 female mice starting at 18 weeks of age with lupus nephritis (LN), curcumin induced the protective effects at least in part by its interaction with regulatory T (Treg) cells Preclinical in vivo [ 18 ] Trans-anethole (FEO) (130 mg/kg FEO, thrice weekly for 1 week, by rubbing on shaved rat dorsal area) ( Foeniculum vulgare Mill. – Apiaceae) In six rats, hepatic dysfunction study indicates promising significant amelioration of liver function reflected in ALT, AST, alkaline phosphatase (ALP), bilirubin, albumin plasma levels by FEO treatment Preclinical in vivo [ 47 ] Trans-anethole (FEO) (36.4, 72.8 or 145.6 mg/kg) once per day for 7 consecutive days ( F. vulgare ) In acute lung injury (ALI)-bearing mice, FEO treatment eliminated LPS‑induced histopathological changes, decreased the number of inflammatory cells, and reduced in IL-17 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…), studies were found for ACE activity [ 39–43 ], reverted serum albumin levels [ 24 , 34 , 44–50 ], decreased of the plasma levels of CRP [ 21–23 , 25 , 32 , 33 , 36 , 51–55 ], transferrin saturation [ 31 , 38 , 56 ], T cells regulation [ 25–29 , 35 , 37 , 57–65 ], haptoglobin levels decreased [ 30 ], APO A-I concentrations decreased [ 20 , 66 ]. Compounds of interest reversed these activities, but in contexts unrelated to SARS-CoV-2, except for two studies.…”
Section: Resultsmentioning
confidence: 99%
“…During the gradual shaping of the tumor immunosuppressive microenvironment, various cytokines are considered to serve a crucial role in regulating the composition and proportions of the cancer-promoting immune cell component and the cancer-suppressing immune cell component (93). Curcumin, as a tumor inhibitor, not only facilitates the secretion of cancer-promoting cytokines, but also inhibits the secretion of cancer-suppressing cytokines, thereby remodeling the tumor immunosuppressive microenvironment (94). IL-2 plays a dual role, stimulating and inhibiting the tumor immune response.…”
Section: The Role Of Curcumin In Tumor Immunomodulationmentioning
confidence: 99%
“…In the present review, highlighted the role of the tumor immunosuppressive microenvironment in tumor progression and the functions of curcumin in modulating and remodeling the tumor immunosuppressive microenvironment have been highlighted. Curcumin increases the number of effector T cells (78), reduces the infiltration of FOXP3+Tregs (85), inhibits cytokine-induced apoptosis of effector T cells and the expression of tumor immunosuppressive cytokines (87,94), enhances NK cell cytotoxicity and mediates M2 TAM transformation to M1 TAM (101,105), which can change the tumor immunosuppressive microenvironment and lead to the killing of tumor cells. Therefore, given the multiple functions and good biosafety of curcumin in inhibiting tumor progression, as a tumor-preventing food and tumor-assisted therapeutic drug, curcumin has potential in tumor treatment potential in combination with multimodal anticancer therapies.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Curcumin, from turmeric, is another compound that has been extensively studied for its immunomodulatory and anti-cancer properties [127,128]. In studies where model antigens have been administered in animal models, it has been reported that curcumin supplementation increased T follicular helper cells and germinal centre B cells as well as subsequent IgG production [129]. The data on effects of polyphenols on immune cells is increasing, especially in the context of cancer [130], with a lot of research understandably focusing on the effects on Tregs [131].…”
Section: Curcuminmentioning
confidence: 99%